Onfarm trials comparing the local streakdisease susceptible maize with a streakdisease resistant variety in southeastern Zaire - Vogel, W.O.; Berhe, T.; Hennessey, R.D. (1991)
Exploratory survey have identified many constraints to maize production in the South Shaba region of Zaїre. These include maize streak disease, stalk bearing catapillars, low soil fertility, weed infestations, and irregular end-of- season rainfall. There is also a shortage of labour for land preparation and weeding, and a lack of fertilizer.Trials were conducted to remedy some of the production constraints. However, because of certain practical problems, more attention was given to the agronomic and short-term entomological and economic factors. The objectives of the trials were:1. to compare the yield of the local variety and Babungo-3 under farm conditions, 2. to estimate the economic benefit of growing Babungo-3 to the average farm family. 3. to investigate the varietal traits that are responsible for the difference in economic benefit. 4. to compare the response of the two varieties to fert1l1zer. 5. to Investigate whether the improved variety could extend planting time. and 6. to set the stage for future economic studies.